Co-precipitation technique to prepare BiNbO4 powders - Radha, R.; Gupta, U. N.; Samuel, V.; Muthurajan, H.; Kumar, H. H.; Ravi, V. (Ceramics International, 2008)
A simple co-precipitation technique was successfully used for the preparation of pure ultrafine single phase BiNbO4. A standard ammonium hydroxide solution was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. For comparison, BN powders were also prepared by the traditional solid-state method. It is observed that the co-precipitation technique produces BiNbO4 on heating at 600 degrees C, whereas complete phase formation occurs only at 800 degrees C in the solid-state method. The phase contents and lattice parameters were Studied by powder X-ray diffraction (XRD). (C) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: BiNbO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Low temperature synthesis and characterization of BiNbO4 powders - Radha, R.; Muthurajan, H.; Rao, N. Koteswara; Pradhan, Sivaram; Gupta, U. N.; Jha, Ratnesh Kumar; Mirji, S. A.; Ravi, V. (Materials Characterization, 2008)
BiNbO4 powders, a potential microwave dielectric ceramic were prepared by both coprecipitation and solid state techniques. In the former method, an aqueous ammonium hydroxide was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. It is observed that the co-precipitation produces BiNbO4 phase on heating at 600 degrees C, whereas complete phase formation occurs only at 800 degrees C in the case of solid state method. The phase contents and lattice parameters were studied by powder X-ray diffraction. The sequence of the reaction and phase evolution of BiNbO4 were also studied by the X-ray diffraction. The samples were characterized by the differential-thermal/thermo-gravimetric analyses and scanning electron microscopy techniques. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: BiNbO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction